SIFAT KUALITATIF DAN KUANTITATIF SAPI BALI BETINA - zulkarnaiin Gobel; Safriyanto Dako; Nibras Karnain Laya (Jambura Journal of Animal Science, 2021)
The purpose of this study was to determine the qualitative and quantitative characteristics of female Bali cattle in Atinggola District, North Gorontalo Regency, Gorontalo Province. This study used a field experiment method in the form of direct observation and measurement of female Bali cattle based on the total population and livestock density in each village in Atinggola District. A total of 122 female Bali cattle aged 2-4 years were used as samples for observation and measurement. Bali cattle aged 2 3 years have a white pattern on the butt (butt mirror) with clear boundaries of 74.64% and 25.33% without clear boundaries. The white pattern on the feet (socks) is clearly visible with the skin color on the legs 73.33% and 26.67% there is no dividing line between the body color and the white pattern on the legs (socks). Bali cattle aged 3 4 years have a white pattern on the butt (butt mirror) which is clearly demarcated by 63.83% and 36.17% without clear boundaries. The white pattern on the feet (socks) is well defined with body hair color 68.09% and 31.91% there is no clear boundary between body color and pattern color. Female Bali cattle aged 2 3 aged 5.81-25.15, the average body length, chest circumference, and height were 93.91±9.29, 148.78±20.40 and 106, respectively, 10±6.16. Bali cattle aged 34 have a diversity of body size of 5.29-35.17%. The average values of chest circumference, body length, and height were 98.73±10.31, 144.22±14.62, 144.22±14.62, respectively. Female Bali cattle from Atinggola District, North Gorontalo Regency, Gorontalo have qualitative characteristics that do not deviate from native Indonesian Bali cattle. Body size diversity of female Bali cattle aged 2 3 was 5.81-25.15, while Bali cattle aged 3 4 had body size diversity of 5.29-35.17%